Error Juris in Jewish Criminal Law - Enḳer, Aharon (Journal of law and religion, 1994)
Although Biblical law ordains the death penalty for some thirty-six offenses, and whipping is the punishment prescribed for many more, it would be rare in fact for such Biblical punishments to be inflicted under Jewish law. Strict procedural and substantive requirements limit these mandatory Biblical penalties to cases of the most willful and deliberate rebellion against God's rule in the universe. Thus, for example, one prerequisite of these Biblical punishments is that the offender be warned in advance—immediately before he commits the offense - that the act he is about to perform is a violation of God's law and that it will be punished by death or by whipping, as the case may be. Further, for the death penalty to be applied, it is not enough that the offender be warned or even acknowledge that he has heard the warning. Rather, he must also affirm his awareness that God has forbidden the intended conduct and has ordained the specified punishment and he must declare expressly that he will commit the offense nevertheless, thereby "surrendering himself unto death."